2003
DOI: 10.1002/syn.10175
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin‐dependent kinase II is involved in the facilitating effect of clozapine on NMDA‐ and electrically evoked responses in the medial prefrontal cortical pyramidal cells

Abstract: Using the method of intracellular recording in in vitro brain slices, we investigated whether calcium/calmodulin-dependent kinase II (CaMKII) is involved in the facilitating action produced by the atypical antipsychotic drug (APD) clozapine on N-methyl-D-aspartate (NMDA)-induced inward currents and electrically evoked excitatory postsynaptic currents (EPSCs) in pyramidal cells of the medial prefrontal cortex (mPFC). The CaMKII inhibitor, KN-93 (N-[2-(N-(4-Chlorocinnamyl)-N-methylaminomethyl)phenyl]-N-[2-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In our studies, a possible mechanism by which these clinically effective antipsychotic agents attenuated the acute inhibitory effects of dizocilpine on miR-219 concentrations is by decreasing the neurochemical and behavioral deficits associated with NMDA receptor hypofunction. Consistent with this hypothesis, it has been shown that haloperidol and clozapine can facilitate NMDA receptor function (44) and counter the inhibitory effects of dizocilpine on NMDA receptor-mediated transmission (45).…”
Section: Discussionmentioning
confidence: 73%
“…In our studies, a possible mechanism by which these clinically effective antipsychotic agents attenuated the acute inhibitory effects of dizocilpine on miR-219 concentrations is by decreasing the neurochemical and behavioral deficits associated with NMDA receptor hypofunction. Consistent with this hypothesis, it has been shown that haloperidol and clozapine can facilitate NMDA receptor function (44) and counter the inhibitory effects of dizocilpine on NMDA receptor-mediated transmission (45).…”
Section: Discussionmentioning
confidence: 73%
“…In fact, chlorpromazine and other phenothiazine derivatives are recognized calmodulin antagonists and clozapine has been found to reduce ERK1/2-MAPK (Pozzi et al, 2003;Ratnakar et al, 1995). These kinases may play a role in the mechanism of action of those antipsychotics which inhibit their activity, for example, clozapine, chlorpromazine, but not in the mechanism underlying the action of other drugs which enhance ERK-MAPK or CaMK activity (Ninan et al, 2003;Pozzi et al, 2003;Yang et al, 2004). Moreover, the lack of chlorpromazine and clozapine effect on phospho-Ser-133-CREB level rather excluded their action via this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, an involvement of some enzymes, which are known to be changed in schizophrenia and are affected by antipsychotic drugs, that is, PKA, protein kinase C (PKC), protein kinase B (PKB; Akt), glycogen synthase kinase-3 (GSK-3), Ca 2 + /calmodulin-dependent protein kinase (CaMK), and mitogen-activated protein kinase (MAPK), in the inhibitory action of chlorpromazine and clozapine on CRH gene promoter activity was determined (Dwivedi and Pandey, 1999;Dwivedi et al, 2002;Lu et al, 2004;Ninan et al, 2003;Yang et al, 2004). We chose for this study chlorpromazine, a classical antipsychotic drug and a atypical antipsychotic clozapine, because in the first part of study they showed the most potent inhibitory effects on the CRH gene activity.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is dependent on protein kinase A, calcium/calmodulin-dependent kinase II, and SFKs. In the nucleus accumbens, clozapine only affects NR2B subunit-containing NMDARs (Ninan et al, 2003;Wittmann et al, 2005). Subtle misregulation of membrane potential, ligand binding, or tyrosine phosphorylation may have profound effects on NMDAR opening, thus influencing behaviors modulated by this channel (Moghaddam, 2003).…”
Section: Introductionmentioning
confidence: 99%